2019
DOI: 10.2105/ajph.2019.305307
|View full text |Cite
|
Sign up to set email alerts
|

Right-to-Carry Laws and Firearm Workplace Homicides: A Longitudinal Analysis (1992–2017)

Abstract: Objectives. To examine the impact of right-to-carry (RTC) firearm laws on firearm workplace homicides (WPHs) in the United States from 1992 to 2017. Methods. We employed 2 longitudinal methods to examine the average effect (pooled, cross-sectional, time-series analysis) and the state-specific effect (random effects meta-analysis) of RTC laws on WPHs committed by firearms from 1992 to 2017 in a 50-state panel. Both methods utilized a generalized linear mixed model with a negative binomial distribution. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…The common approach to handling interstate variation was to model 2-way fixed effects or conduct state-specific analyses. Alternative methods to explore state-specific deviations from the average effect would be to include a metaanalysis of state-specific effects 20 or the Bacon decomposition for 2-way fixed effects in the presence of varying treatment timing. 53 Authors also differed in their definitions of SYG or expanded castle doctrine laws and tended to focus only on statutory rather than case law.…”
Section: Research and Analysismentioning
confidence: 99%
“…The common approach to handling interstate variation was to model 2-way fixed effects or conduct state-specific analyses. Alternative methods to explore state-specific deviations from the average effect would be to include a metaanalysis of state-specific effects 20 or the Bacon decomposition for 2-way fixed effects in the presence of varying treatment timing. 53 Authors also differed in their definitions of SYG or expanded castle doctrine laws and tended to focus only on statutory rather than case law.…”
Section: Research and Analysismentioning
confidence: 99%
“…An examination of workplace homicide epidemiology from 2011 to 2015 detailed a shift in workplace homicides away from those associated with robberies toward other crimes, indicating that a change in firearm exposure in the workplace, and the public writ large, may be driving this change (Doucette, Bulzacchelli, et al, 2019). A 50-state panel analysis using CFOI data found that right-to-carry laws, or laws that remove restrictions for carrying a concealed handgun in public, increased the incidence of workplace homicides committed with firearms by 29% over a 26-year period (Doucette, Crifasi, et al, 2019). Yet, both of these analyses raised the same limitations surrounding CFOI data, limitations that likely underestimate the true magnitude of violence associated with a workplace homicide incident (Doucette, Bulzacchelli, et al, 2019; Doucette, Crifasi, et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A 50-state panel analysis using CFOI data found that right-to-carry laws, or laws that remove restrictions for carrying a concealed handgun in public, increased the incidence of workplace homicides committed with firearms by 29% over a 26-year period (Doucette, Crifasi, et al, 2019). Yet, both of these analyses raised the same limitations surrounding CFOI data, limitations that likely underestimate the true magnitude of violence associated with a workplace homicide incident (Doucette, Bulzacchelli, et al, 2019; Doucette, Crifasi, et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Efforts to uncover these elements have revealed some promising targets for study and have become increasingly broad in scope. These include modifiable social determinants of health (including poverty, socioeconomic support, education and access to healthcare), behavioral factors (alcohol and drug use, firearm ownership), and specific firearm restrictive laws (stand your ground, risk based firearm restriction laws, concealed carry, background checks, and handgun specific policies) 5–39 …”
mentioning
confidence: 99%